FAKTOR-FAKTOR YANG BERHUBUNGAN DENGAN TINGKAT DEPRESI PADA PASIEN KANKER YANG MENJALANI KEMOTERAPI DI RUMAH SAKIT Dr. OEN SURAKARTA - Tunjung Sri Yulianti; Listriana Intan Kurniawati (Sekolah Tinggi Ilmu Kesehatan Panti Kosala, 2018)
Background: Suffering from cancer is a prominent stimulus for patients, so it can clearly bring great mental stress and suffering to the patient. Cancer patients undergoing chemotherapy usually experience various symptoms as a result of the disease or from chemotherapy itself. These symptoms affect the patient both physically and emotionally and furthermore negatively affect the treatment. Depression is a common symptom in cancer patients that are difficult to detect. This condition can negatively affect the quality of life of patients. Patient response to cancer can be affected by past life experiences with the disease. Each client uses different coping strategies. Support provided, will provide great benefits for subsequent therapy, prognosis and improvement of patient's quality of life. Objective: To know the factors related to depression level in cancer patients who underwent chemotherapy at Dr. OEN SURAKARTA Hospital. Research subjects: Cancer patients undergoing chemotherapy. Keywords: Frequency of chemotherapy, stage of cancer, coping mechanism, family support, depression level